USING SHORT STORY TO IMPROVE STUDENTS’ VOCABULARY ACHIEVEMENT OF THE GRADE IX STUDENTS OF SMP NEGERI 6 PANGSID SIDRAP REGENCY - Hayati Hayati (Publikasi dan UKI Press UKI Toraja., 2022)
The objective of the research was (1) to find out whether or not the use of short story to improve the students’ vocabulary achievement of Grade IX Students of SMP Negeri 6 Pangsid, (2) to find out which aspect of vocabulary was dominantly affected by short story at SMP Negeri 6 Pangsid. This research employed the method of the research was quasi-experimental research method. Two classes were selected using cluster random sampling technique, 25 students each. One by experimental group, and the other by control group. The experimental group was taught by short story method and the control group was taught by non-short story or conventional method. The data were collected use vocabulary test administered to experimental group and control group before and after treatment. The treatment was conducted for eight meetings for experimental group and control group. The data was analyzed using SPSS 20.0 version. The result of the t-test value in posttest (20.294) was higher than t-table (2.010) while the t-test value of control group (4.164). This means that H1 was accepted. The research concluded that (1) teaching vocabulary by using short story increased the students’ vocabulary at the ninth year of SMP Negeri 6 Pangsid and (2) the aspect that most affected was word meaning, it was proven by the interval score was higher among the others aspects (85.20).